2000
DOI: 10.1007/bf03167689
|View full text |Cite
|
Sign up to set email alerts
|

The role of cardiac troponin I in determining the necessity for exercise electrocardiography in low risk patients with chest pain

Abstract: CTnI in the normal range can identify patients with acute chest pain who have a negligible event rate and for whom exercise electrocardiography is not required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Indeed, the serum troponin level provides a valuable insight into the morphological basis of ACS, in that angiographic studies have shown that elevated troponin levels are more likely to be associated with the presence of complex atheromatous lesions and visible thrombus formation [14,17,19]. The degree of elevation of troponin could also guide the preference for the specific pharmacological or other intervention modality, as with the use of enoxaparin [20], platelet receptor antagonists such as tirofiban and abcimixab [21,22] and procedures including coronary angioplasty, percutaneous transluminal coronary angioplasty, stent insertion, rotational atherectomy and stress testing [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the serum troponin level provides a valuable insight into the morphological basis of ACS, in that angiographic studies have shown that elevated troponin levels are more likely to be associated with the presence of complex atheromatous lesions and visible thrombus formation [14,17,19]. The degree of elevation of troponin could also guide the preference for the specific pharmacological or other intervention modality, as with the use of enoxaparin [20], platelet receptor antagonists such as tirofiban and abcimixab [21,22] and procedures including coronary angioplasty, percutaneous transluminal coronary angioplasty, stent insertion, rotational atherectomy and stress testing [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Lindahl et al [31], in a re-analysis of the FRISK data [17], have demonstrated improved NPV of considering peak troponin T at a lower discriminator level (<0.06 ng/ml). In an analysis, at our department, of 98 patients presenting to the emergency room with a history of resting chest pain but no electrocardiographic change, peak cTnI of less than 0.03 ng/ml (Beckmann Access population 98th percentile value) was associated with a 6-month event-free follow-up [32]. Identification and early discharge of such patients may present considerable health care cost saving and further trials examining the important area of cut-point selection are warranted.…”
Section: Discussionmentioning
confidence: 99%